2004
DOI: 10.1055/s-2004-817819
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin/Leptin-Imbalance in Patients with Primary Biliary Cirrhosis

Abstract: Our data confirm in PBC patients that serum bound leptin levels are increased and clearly show a parallel decrease in serum ghrelin concentrations acting as a physiological counterpart to leptin. Furthermore, we suggest that these changes are linked to the insulin resistance observed in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…The severity of liver disease was (median and range), according to ChildPugh: 9 (5-12) and the MELD: 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Albumin (median and range) was decreased in liver failure patients when compared with the Cont group, 3.0 (2.6-4.6) vs 4.1 (3.4-5.3) g/dl, PZ0.009.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The severity of liver disease was (median and range), according to ChildPugh: 9 (5-12) and the MELD: 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Albumin (median and range) was decreased in liver failure patients when compared with the Cont group, 3.0 (2.6-4.6) vs 4.1 (3.4-5.3) g/dl, PZ0.009.…”
Section: Resultsmentioning
confidence: 95%
“…In the study by Marchesini et al (18), ghrelin levels were not increased in cirrhosis but increased with decreasing Corli score, a method used to quatify and score the amount of ingested food, and along the scale of anorexia/hunger. In patients with primary biliary cirrhosis, Breidert et al (22) found that serum ghrelin levels were decreased in comparison with the Cont group. We have recently found significantly decreased fasting and post-OGTT plasma ghrelin levels in patients with liver failure who were candidates for transplantation when compared with Cont subjects (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, patients with liver cirrhosis had a lower energy intake, higher resting energy expenditure (Kalaitzakis et al, 2007), higher fasting sugar (Kalaitzakis et al, 2007(Kalaitzakis et al, , 2009) and leptin levels (Breidert et al, 2004;Ataseven et al, 2006;Kalaitzakis et al, 2007Kalaitzakis et al, , 2009, and higher insulin resistance (Kalaitzakis et al, 2007(Kalaitzakis et al, , 2009. Plasma fasting total ghrelin levels were found to be either unchanged (Marchesini et al, 2004;Kalaitzakis et al, 2007Kalaitzakis et al, , 2009, elevated (Tacke et al, 2003;Ataseven et al, 2006), or decreased (Breidert et al, 2004;Diz-Lois et al, 2009) in patients with cirrhosis compared with control subjects.…”
Section: Ghrelin Gene Products In Food Intake and Gut Motilitymentioning
confidence: 91%